IDENTIFYING IMPACT EVENTS WITHIN THE LUNAR CATACLYSM FROM 40AR-39AR AGES AND COMPOSITIONS OF APOLLO 16 IMPACT MELT ROCKS - Norman M.D.; Duncan R.A.; Huard J.J. (My University, 2006)
Lunar impact melt breccias provide a unique record of the timing and frequency of collisional events during the early history of the inner Solar System prior to the development of a significant rock record on Earth. The predominance of ages clustering between 3.8 and 4.0 Ga was a major, unexpected discovery obtained from geochronological studies of lunar impact melts, and is the basis of the concept that a cataclysmic bombardment of large planetesimals struck the Earth and Moon, and possibly the entire inner Solar System, about 3.85 ± 0.10 billion years ago. As a test of the cataclysm hypothesis, we measured high-resolution (20-50 steps) 40Ar-39Ar age spectra on 25 samples of Apollo 16 impact melt breccias using a continuous laser heating system on sub-milligram fragments. Twenty-one of these 25 breccias produced multi-step plateaus that we interpret as crystallization ages, with 20 of these ages falling in the range 3.75-3.96 Ga. We propose that at least four different melt-producing impact events can be distinguished based on the ages, bulk compositions, and petrographic characteristics of Apollo 16 melt breccias. The recognition of multiple impact events within the Apollo 16 melt breccia suite shows that numerous impact events occurred on the lunar surface within a relatively narrow time interval, providing additional evidence of a heavy bombardment of the Moon during the early Archean. © 2006 Elsevier Inc. All rights reserved.
Keywords: Archean; Archean; Precambrian::Archean; Докембрий::Архей; Precambrian::Archean